Pengaruh Profitabilitas dan Nilai Perusahaan terhadap Volume Perdagangan Saham Pada LQ45 - Ell Bryan Timothy; Francis M. Hutabarat (Universitas Batanghari Jambi, 2022)
Companies tend to have the main focus on seeking maximum profits to attract potential investors. Companies that have the ability to earn profits and have good corporate value can be considered by potential investors in investing. The purpose of this study was to determine the relationship between profitability and firm value on stock trading volume partially and simultaneously. The sample taken for this study revealed 28 companies from companies listed on LQ45 in the 2017–2020 time span, respectively. This research uses several analyses such as descriptive analysis, linear regression interpretation, classical assumption test, f-test, t-test, and coefficient of determination with the help of the SPSS program. The results obtained are profitability does not affect stock trading volume, firm value has a significant effect on stock trading volume, and simultaneously profitability with firm value has a significant effect on stock trading volume.